Pengembangan E-Modul Berbasis Model Experiential Learning dengan Pendekatan Berdiferensiasi untuk Meningkatkan Pemahaman Konsep dan Keterampilan Kolaborasi Peserta Didik - Wahyu Prasetya Pratama; I Komang Werdhiana; Haeruddin Haeruddin; Muslimin Muslimin; Nurasyah Dewi Napitupulu (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
Development of e-modules based on experiential learning models with a differentiated approach for students' learning needs. This study aims to: (1) produce a level of feasibility of e-modules based on experiential learning models with a differentiated approach; (2) test the effectiveness of e-modules based on experiential learning models with a differentiated approach; (3) determine the practicality of e-modules based on experiential learning models with a differentiated approach. This study is a Research and Development (R&D) study using the 4D development procedure. The subjects of the study were students of class X of SMA Negeri 5 Palu. The data collection technique used test and non-test instruments. The results of instrument validation by material experts and media experts showed that the instruments were feasible to use in the study. The data analysis techniques used were descriptive analysis and MANOVA tests. The results of the study showed that (1) the e-modules based on experiential learning models with a differentiated approach produced met the feasibility criteria based on expert validation with a feasible category and practitioner validation with a very feasible category; (2) e-modules based on experiential learning models with a differentiated approach are effective in increasing conceptual understanding with an effect size of 1.3 in the high category but less effective in increasing collaboration skills with an effect size of 0.4 in the low category; (3) e-modules based on experiential learning models with a differentiated approach are practical in learning physics on the topic of global warming: concepts and solutions.